The use of the international classification of ICNP® in relation to the 13 canons of Florence Nightingale in planning the resident’s care in a British nursing home - Ozga, Magdalena; Bikowska, Magdalena; Gorzkowicz, Bożena; Skirmuntt, Martyna (Nursing Problems / Problemy Pielęgniarstwa, 2018)
In 1860 in England the book “Notes on Nursing, What it is, and What it is Not” was published by Florence Nightingale. The canons included there have revolutionized the care of the sick people, contributing to a significant improvement in the living conditions of patients under nursing care. These principles have also become the basis for creating guidelines in the form of algorithms and nursing procedures. International Classification for Nursing Practice is a system and also a tool that enables nurses from around the world to conduct professional practice in the area of ​​patient care through a standardized language system. The aim of the presented work was to find of Florence Nightingale’s canon content in the diagnosis of patient care problems contained in the International Classification for Nursing Practice, ICNP®. It was presented on the example of taking care of a pensioner in one of the British Seniors’ Houses.